Fibrous hamartoma of infancy: A case report - Taşkin, Erdal; Kiliç, Mehmet; Özercan, I. Hanifi; Yilmaz, Erdal; Varol, Ilknur; Aygün, A. Denizmen (My University, 2004)
Fibrous hamartoma of infancy is an uncommon, self-limiting benign tumor that presents during the first two years of life, developing from subcutaneous fibrous tissue proliferation at almost any site. A male child aged eight months was accepted at our clinic because of painless mass at left axilla since two months. This mass was histopathologically described as fibrous hamartoma of infancy and is presented because of its rare appearance.
İnfantil fibröz hamartom: Bir vaka takdimi
Keywords: Fibrous hamartoma of infancy; Soft tissue tumor